Kone- ja metallialan koulutuksen laadullinen ennakointi - Hannu Hernesniemi (The Research Institute of the Finnish Economy (ETLA), 2012)
– Machinery and metal products industry employs about 130,000 people in Finland and another 100,000 people in foreign subsidiaries of Finnish companies. This report focuses on this sector's qualitative or substantive projections for vocational education and training (vocational schools and polytechnics). The starting point was a relatively rich body of research studies on future changes in the sector's job tasks and functions, which are listed in the bibliography. Based on these studies the researcher and the training committee identified the five most important future areas of expertise and related trends, which are as follows: i) customer know-how, where solution orientation and deep understanding of clients generate value for clients, ii) research and development, the importance of which is continually growing in their operations iii) the internationalization of production networks in the wake of globalization as especially leading companies seeking to manage production and marketing on a continent-by-continent basis, iv) information technology and increasing automation of intelligence in machines and automation processes, and v) energy and environmental expertise, because it is precisely these areas that will spawn new businesses. In the future educational co-operation with other sectors should be increased regarding the application of ICT to machinery, goods, and industrial processes, teaching of procurement and skills required in international research, development and innovation (RDI), such as teaching of languages, cultures and marketing. This is a pilot study. In the future a systematic analysis should be carried out based on surveys designed to pinpoint the sector's main job tasks, their frequency and importance. The result of this study would be the specification of the main job categories and job profiles of professionals in this field. Experts in this sector could be asked to assess the changes going on in these areas. This information can be used to plan the future development of curricula and teacher training so that the new educational demands can be met.
Keywords: L61; L62; L64; I25; O30; 330; Machinery and metal products industry; education and training; qualitative projections